Some Extensions of Fixed Point Results over Quasi-JS-Spaces. (28th April 2016) - Noorwali, Maha; Alsulami, Hamed H.; Karapınar, Erdal
Abstract : We introduce the notion of quasi-J S -metric space. After defining the basic topological properties of quasi-J S -metric space, we investigate fixed point of certain mapping in the frame of complete quasi-J S -metric space. Our results unify and cover several existing fixed point theorems in distinct structures (such as standard quasi-metric spaces, quasi-b -metric spaces, dislocated quasi-metric spaces, and quasi-modular spaces) in the literature.